Critical appraisal of medical devices in the management of cerebrovascular disease - Michael J Schneck (Dove Medical Press, 2008)
Michael J SchneckDepartments of Neurology and Neurological Surgery, Loyola University Chicago, Stritch School of Medicine, Maywood, Illinois, USAAbstract: Medical devices may revolutionize the management of acute ischemic stroke and prevention of recurrent events. By comparison with pharmaceuticals, the device approval process and subsequent application of these devices in stroke treatment is founded on a paucity of Class I evidence-based clinical trial data. Thromboembolectomy for acute stroke, stenting of cervical or cerebral arteries for stroke prevention, and percutaneous closure of patent foramen ovale for prevention or recurrent cerebral ischemia are being done with an ever-increasing frequency despite few, if any, randomized clinical trials to confirm the appropriateness of the interventions. The current basis, or lack thereof, for these interventions for cerebrovascular disease is therefore discussed. As such, a critical appraisal of the available clinical data does not support widespread use of medical devices at this time outside of well-designed clinical trials.Keywords: medical devices, stroke, PFO closure, stents, clot retrieval devices, clinical trials